The strategy of domestic wastewater management in Kenjeran Surabaya - Daniel Wicaksono; Agus Slamet (Sustinere: Journal of Environment and Sustainability, 2017)
Kenjeran is one of the districts in Surabaya classified as high-risk in terms of sanitation, based on the EHRA Surabaya 2012 report. Kenjeran consists of four sub-districts: Bulak Banteng, Tanah Kali Kedinding, Sidotopo Wetan, and Tambak Wedi. Among these, Bulak Banteng, Tanah Kali Kedinding, and Tambak Wedi have been identified as areas where open defecation still occurs.This research is a descriptive study conducted through field surveys, interviews, and comparisons of existing conditions with applicable standards and regulations. The technical aspect of the study involved analyzing the need for wastewater infrastructure facilities based on the volume of domestic wastewater.To address domestic wastewater management in the four sub-districts, 80 communal Sewage Treatment Plants (STPs) were designed. Each STP was planned to serve between 75 and 100 households. The domestic wastewater treatment system utilized Anaerobic Baffled Reactor (ABR) technology. An example of an STP design was carried out in Dukuh Bulak Banteng, covering 100 households.